Defect Sizing Using Non-destructive Ultrasonic Testing Applying Bandwidth-Dependent DAC and DGS Curves - Kleinert, Wolf.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a precise approach for defect sizing using ultrasonics. It describes an alternative to the current European and American standards by neglecting their limitations. The approach presented here is not only valid for conventional angle beam probes, but also for phased array angle beam probes. It introduces an improved method which provides a significant productivity gain and calculates curves with high accuracy. Its content is of interest to all those working with distance gain size (DGS) methods or are using distance ampllitude correction (DAC) curves.
Preface -- Sizing Methods: Distance Gain Size (DGS) and Distance Amplitude Correction (DAC) -- A new approach to bring DGS and DAC close together -- Diagrams -- Perspectives.
Keywords: Materials -- Analysis; Mechanics, Applied; Solids; Manufactures; Characterization and Analytical Technique; Solid Mechanics; Machines, Tools, Processes